(untitled) (Research, Society and Development, 2019)
This article presents the problem of evasion at Luiz Girão High School, located in the municipality of Maranguape in the State of Ceará, Brazil. Our research refers to the period between 2013 and 2017. School dropout engenders discussions with emphasis on the first-grade classes of high school, the final stage of basic education in Brazil. The methodology used for the analysis of this phenomenon was based on a case study, taking as reference the quantitative and qualitative research applied, using the questionnaire technique, carried out with fifteen (15) students evaded between the years of 2013 and 2017, who returned to school after the four year period. As a central question, one has: "What are the real motivations that led to their avoidance in basic education, especially in the first year of high school?” The objective of this study was to know some of the causes that contributed to the dropout and consequent evasion of a certain number of students of the 1st grade of High School. The results indicate that the causes of evasion in 40% reflect external factors to the school environment, that is, they were causes related to employment, work, income, health. In this sense, the present case study found that the premises of evasion are multifactorial and reverberate for school retention.